2016
DOI: 10.1371/journal.pone.0164034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Latent Tuberculosis among Health Care Workers in High Burden Countries: A Systematic Review and Meta-Analysis

Abstract: BackgroundTuberculosis is one of the leading causes of death worldwide. Twenty-two high burden countries contributed to the majority of worldwide tuberculosis cases in 2015. Health care workers are at high risk of acquiring tuberculosis through occupational exposure.ObjectiveTo estimate the prevalence of latent tuberculosis infection (LTBI) among health care workers in high burden countries.MethodsDatabases including MEDLINE (Ovid), EMBASE (Ovid), CINAHL (Ovid) and ISI Web of Science (Thompson-Reuters), and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
59
4
16

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 40 publications
(49 reference statements)
14
59
4
16
Order By: Relevance
“…1 Previous studies have demonstrated that the overall prevalence of LTBI among HCWs was 37%, 2 ranging from 7.2%-14.9% in low-burden countries 5,6 to 47% in high-burden countries. 7 A review article by Menzies et al 4 reported that the median prevalence of LTBI was 63% (33%-79%) among HCWs in low-to middle-income countries, and 24% (4%-46%) among HCWs in highincome countries. Therefore, the baseline prevalence of LTBI among HCWs in our study reflects that in low-burden high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies have demonstrated that the overall prevalence of LTBI among HCWs was 37%, 2 ranging from 7.2%-14.9% in low-burden countries 5,6 to 47% in high-burden countries. 7 A review article by Menzies et al 4 reported that the median prevalence of LTBI was 63% (33%-79%) among HCWs in low-to middle-income countries, and 24% (4%-46%) among HCWs in highincome countries. Therefore, the baseline prevalence of LTBI among HCWs in our study reflects that in low-burden high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…The documented 3 to 6-fold increased risk of TB is due to persistent occupational TB exposure in the setting of absent or poorly implemented TB infection control (TB-IC) programmes 2,11 and a high prevalence of undiagnosed TB in healthcare facilities 22,23 . Ironically, accurate data on TB exposure and infection risk in HCWs is most limited from settings with highest TB burden 9,24 . Possible factors explaining the paucity of occupational TB data include the lack of national HCW TB surveillance, weak or non-existent occupational health programmes, reluctance among HCWs to disclose a TB diagnosis owing to stigma and the challenge of diagnosing latent TB infection in TB endemic settings 25 .…”
Section: Challengesmentioning
confidence: 99%
“…Certain risk factors that increase the likelihood of developing active TB have been identified such as HIV, diabetes and tobacco use. However, in other populations that include HCWs, who are more likely to have latent TB infection (LTBI) than the general population 24 , it is not possible to predict who will develop active TB. IPT or alternative LTBI treatment regimens have been recommended in high and low incidence settings for groups at high risk of TB reactivation, such as people living with HIV and contacts of patients with pulmonary TB 79 .…”
Section: Ongoing Scientific Challengesmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] A systematic review showed that the incidence of latent Mycobacterium tuberculosis infection (LTBI), demonstrated by converting the tuberculin skin test (TST), can reach 14% in these professionals; and the risk of developing TB disease is 5,361 cases/100,000 health workers every year due to nosocomial exposure. 9 In a multicenter been held in Brazil, identified a high prevalence of LTBI among health professionals in primary care through two diagnostic tests (TST and Interferon-gamma Release Assays-IGRA): 40% and 27%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, few studies explore this theme in other professions, either in Brazil or worldwide. 8,[11][12][13][14] It is necessary to verify the proportion of the disease among other occupational groups to determine the character of occupational TB.…”
Section: Introductionmentioning
confidence: 99%